Responsabilidad jurisdiccional del estado por aplicación de la carga dinámica probatoria en materia penal bajo la égida de la Ley 600 de 2000 (2016)
The present article is the result of the analysis of different orders of the Criminal Chamber of the Supreme Court of Justice of Colombia, which has applied the doctrine called "dynamic load evidence" in processes judged under Law 600 of 2000, and responsibility that this implementation can generate the state. With the understanding of guarantees like presumption of innocence and in dubio pro reo, is concluded that the doctrine mentioned breaks them, hence it is possible to impute responsibility to the State for jurisdictional error.